Glansbilledets skyggeside: Negativitetens plads i 1800-tallets religiøse kunst - Burmeister, David; Wangsgaard Jürgensen, Martin (Periskop – Forum for kunsthistorisk debat, 2023)
The 19th century saw a remarkable innovation of the subject-matter of Danish altarpaintings. Frequently depicting the ministry of Christ and his Glory, these paintings have often been criticized for being skillfully executed but lacking drama, being overly sweet or even sentimental. This article argues that, in spite of the glossy façade, these paintings often engage in far more sinister topics of life and of faith. The article argues that Søren Kierkegaard’s theology offers a superb lens for gaining insights into this side of the religious painting of the so-called ‘Golden Age’ of Danish art and explores the ‘shadows of the glossy images’ through close readings of Danish altar pieces ranging from Bertel Thorvaldsen’s seminal Christ and C. W. Eckersberg’s ground-breaking Incredulity of Thomas to late 19th Century works of art by Constantin Hansen and Anton Dorph. The main argument of the article is that a negative understanding of this world and not least the constant struggle between being separated from, but needing to get (spiritually) closer to the Saviour remain very strong themes in the religious paintings throughout the 1800s, albeit mainly offered as a personal experience and not as a part of the ideal Christ figure.